Informed Trading by Advisor Banks: Evidence from Options Holdings - Lowry, Michelle; Rossi, Marco; Zhu, Zhongyan (Review of Financial Studies, 2019)
Strong conflicts of interest exist within investment banks: the investment banking division possesses substantial private information, and the asset management division seeks such information. This raises the question of whether the asset management division benefits from an information advantage on client firms. While prior examinations of advisor bank trading in client firms have focused on stocks and found mixed results, we argue that the options market represents a more attractive venue for such trading. We find significant evidence of advisor banks trading in client firm options ahead of merger announcements, but no evidence of similar trading in client firm stock. Received October 22, 2015; editorial decision June 5, 2018 by Editor Philip Strahan. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.